2021
DOI: 10.9734/jpri/2021/v33i59b34428
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Activity of Drugs is an Important Factor of Their Local Action at the Injection Site: What We Don't Use to Prevent Post-Injection Abscesses

Abstract: It is established that very few modern high-quality drugs in the dosage form "Solution for injection" have isoosmotic activity in the range of 280-300 mosmol/l of water. The main part of solutions for injection is hypotonic or hypertonic solutions, which can have osmotic activity in the range of 0 - 4000 mosmol/l of water. The reason for this was that the osmotic activity of drugs is not included in the list of controlled indicators of drugs quality, so it is not subject to control. It is shown that the osmoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 4 publications
(5 reference statements)
0
28
0
Order By: Relevance
“…However, in recent years, the cause of postinjection inflammation, necrosis and abscess has finally been established. It has been shown that the cause of Nicolau syndrome is a very strong local irritating effect of medicinal solutions [26]. This became possible because the local irritating effect of drugs on tissues at injection sites is not controlled, as it is not included in the standard of drug quality control [27].…”
Section: Sources Of the Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in recent years, the cause of postinjection inflammation, necrosis and abscess has finally been established. It has been shown that the cause of Nicolau syndrome is a very strong local irritating effect of medicinal solutions [26]. This became possible because the local irritating effect of drugs on tissues at injection sites is not controlled, as it is not included in the standard of drug quality control [27].…”
Section: Sources Of the Problemmentioning
confidence: 99%
“…It has been shown that in addition to this, the standard for quality control of medicines does not include an assessment of their osmotic activity [28]. In addition, it has been shown that the drug quality control standard allows for the presence of high acidic or high alkaline activity in some medicinal solutions [26][27][28]. It is reported that drug solutions considered to be of high quality today may have isotonic and weak alkaline activity, but sometimes (in some serial numbers or in some pharmaceutical companies) drugs by chance (by ignorance) may have hypotonic or hypertonic activity, high acid or alkaline activity, as well as a strong local irritant effect, which in some cases, it can transform into a cauterizing effect [26].…”
Section: Sources Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations